PENGARUH DONGENG TERHADAP ANAK DALAM MEMPERSEPSI KECERDASAN (PERSPEKTIF MULTIPLE INTELLIGENCES-HOWARD GARDNER) - Heru Kurniawan (Pusat Studi Gender dan Anak (PSGA) IAIN Purwokerto, 2017)
Humans are gifted by God with eight intelligences (multiple intelligences). They are: linguistic, logical-mathematical, spatial, bodykinesthetic, musical, interpersonal, intrapersonal, and naturalist. Adult (parent) and children also need to understand the concept of the holistic intelligence. People can start early.Children are like stories (homo fabulans) and beings who loved playing (homo ludens). So, to be able to develop intelligence to the fullest, parents need a tool that can trigger such creativity. Fairy tale is one tool that can be used to reach it. In fairy tales summarized the various aspects required in the process of development of intelligence such as language (linguistic), the storyline (the logic of the story), social sensitivity (interpersonal and intrapersonal), conflict (the rhythm), imagination (visual/spatial), movement (kinesthetic), and nature (naturalist) that can be used as a real picture or the prototype for the child to get to know aspects of intelligence they have.